Frictional Axial Resistance of Clamped Split Pocket Mechanism Steel Structural Joint: An Experimental Study - Putra, Whelly T.; Setiawan, Angga F.; Saputra, Ashar; Satyarno, Iman; Pratama, Hamdi Y. (Civil Engineering Journal, 2024)
The Clamped Split Pocket Mechanism (CSPM) prefabricated joint system was developed for a single-story steel instant house, designed to be compact and rapidly constructed without modifying the end of the beam and column element member. The CSPM bolted joint system was proposed as an optimal solution for post-disaster housing, especially after earthquakes. Despite its potential, the frictional tensile resistance behavior of the CSPM bolted joint system has not been previously studied, necessitating experimental investigation. This study examined the frictional tensile resistance behavior of the CSPM joint system by monitoring the effective friction coefficient under axial tension force. The experiments considered both the strong and weak axes of the joint and utilized two configuration types of specimens (L and T) with varying bolt pretensions of 2.5, 5, 7.5, and 10 kN. Results indicated that the effective friction coefficient of the CSPM bolted joint system ranged from 0.19 to 0.26, correlated to bolt pretension. Increased bolt pretension resulted in larger surface deformation of the split pocket, triggering a not uniform frictional tensile resistance across the steel surfaces of the split pocket joint. From this study, the achieved effective friction coefficients could guide the design of minimum pretension forces for clamps in prefabricated steel instant houses. Doi: 10.28991/CEJ-2024-010-09-07 Full Text: PDF